Analysis of the Impact of Shopee's Double Days Festival Online Shopping Promotion Strategy on User Participation Intention (Study on Millennial Generation Shopee E-Commerce Users) - Muhammad Ilham Maulana; Anton Agus Setyawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aimed to analyze the impact of Shopee's double days festival online shopping promotion strategy on user participation intentions (Study on Millennial Generation Shopee E-Commerce Users). This research is a type of quantitative descriptive research. The population in this study were all millennial generation Shopee e-commerce users spread throughout Indonesia. The sample size of this study was 150 respondents. The sampling technique used was non-probability, with purposive sampling. This research uses primary data. The data collection technique used was a questionnaire. This analysis process was carried out using the Smart PLS 3.2 application. The results of this study show that the Perceived temptation of price promotion has a positive and significant influence on participation intention. This means that the higher the perceived temptation of price promotion, the higher the participation intention. Perceived fun of promotion activities positively and significantly affects participation intention. This means the higher the perceived fun of promotion activities, the higher the participation intention. Perceived category richness of promotion positively and substantially influences participation intention. This means the higher the perceived categories' richness of promotion, the higher the participation intention.